Formation of the reaction zone between tin‐copper brazing fillers and aluminum‐silicon‐magnesium alloys: Experiments and thermodynamic analysis: Bildung der Reaktionszone zwischen Zinn‐Kupfer‐Lot und Aluminium‐Silizium‐Magnesium‐Legierungen: Experimente und thermodynamische Berechnungen. Issue 12 (10th January 2018) - Bobzin, K.; Öte, M.; Wiesner, S.; Schmidt, A.; Apel, M.; Berger, R.; Aretz, A.; Mayer, J.
Abstract: A primary challenge in brazing is the controlled formation of phases resulting from interactions of elements of the liquid filler metal with those of the base material. The morphology of the brazed joint, which is decisive for the mechanical properties of the joint, is influenced by present elements and process parameters such as brazing temperature and time. Furthermore, the wetting of the base material is a crucial factor in joining of aluminum because of the low wettability of the alumina layer by molten brazing filler metals. In order to remove the alumina and prevent reoxidation of the substrate surface, the brazing process can be conducted in vacuum or inert gas atmosphere. Again, selection of process parameters is crucial for the quality of the brazed seam. In this work, we focus on the influence of the process parameters on the wetting behavior and the formation of aluminum‐copper phases theoretically by means of thermodynamic calculations using a CALPHAD database as well as by means of in‐situ observations in the large‐chamber scanning electron microscope (LC‐SEM) and by brazing experiments. Both the critical temperatures with respect to the wetting and the reaction kinetics as well as the crucial stages of the brazing process and the resulting phases were determined.